Navigating the online-offline continuum: exploring victims, spaces, and dangers - Munk, Tine (Victimisation in the digital age, 2025)
This chapter examines the multifaceted dangers present across urban landscapes, digital spaces, and interactions with non-human entities, highlighting the complexities of the Online-Offline Continuum Approach. It delves into issues such as privacy violations, boundary transgressions, and exploitation, encompassing diverse contexts from public streets to online platforms by exploring how blurred boundaries between physical and digital realms contribute to the proliferation of non-consensual imagery, harassment, and wildlife exploitation. Drawing on examples ranging from urban development projects to online animal cruelty, the chapter explores the interconnectedness of human and non-human experiences in the digital age.